Isolation of fucoxanthin and fatty acids analysis of Padina australis and cytotoxic effect of fucoxanthin on human lung cancer (H1299) cell lines - Jaswir, Irwandi; Noviendri, Dedi; Mohd. Salleh, Hamzah; Bakhtiar, M. Taher; Kazuo , Miyashita (Academic Journals, 2011)
Fucoxanthin has been successfully isolated from species of Malaysian brown seaweed, namely Padina australis. The purity of the fucoxanthin is >98% as indicated by high performance liquid chromatography analysis. This seaweed also contains a considerable amount of unsaturated fatty acids. Thirteen fatty acids were detected with gas chromatography. However, fatty acid methyl ester (FAMEs) of eicosapentanoic acid (C20:5n-3), arachidonic acid (C20:4n-6), linoleic acid (C18:2n-6) and alpha-linolenic acid (C18:3n-3) contents of P. australis were found to be 2.06, 9.50, 6.37, and 2.83%, respectively. For saturated fatty acids, palmitic acid (C16:0) was found to be the major fatty acid with about 23.97%. Furthermore, data obtained from the methyl thiazolyl tetrazolium (MTT) assay indicated that fucoxanthin reduced the viability of H1299 cell lines, showing an IC50 value of 2.45 mM.